A Very Low Temperature Growth of BaTiO3 Nanoparticles by Sol‐Hydrothermal Method. Issue 23 (17th October 2022) - Kumar, Dushyant; Kumar, Sahil; Kumar, Shammi; Thakur, Nagesh; Shandilya, Mamta
Abstract : Low‐temperature intercessions are the most proficient technique to control the particle size in the nanometres range with low agglomeration. Herein, BaTiO3 (BT) nanoparticles (NPs) are prepared at low temperatures by using the sol‐hydrothermal technique. An X‐ray diffraction (XRD) pattern of the powder signifies the pure tetragonal phase, and the average crystallite size (43.2 nm) is calculated using different methods: Scherrer's, uniform deformation model (UDM), uniform stress deformation model (USDM), and uniform deformation energy density model (UDEDM) analysis, and the structure is refined by Rietveld refinement method with a good fit value ( χ 2  = 1.66). Spherical and uniform surface morphology is counted up for BT NPs. Under suitable conditions, BT NPs can be prepared with an average particle size of ≈115 ± 10 nm. However, after sintering, the average grain size (335 ± 10 nm) of the BaTiO3 nanopowder is found to increase with dense grain boundaries. The dielectric behavior of the sample is analyzed with the variation of frequency at different temperatures. The effect of grain and grain boundary on the electrical properties of the material is also investigated by using complex impedance spectroscopy (CIS). Abstract : The high‐temperature methodology is less controlled in the crystallization, and the morphology of the products lacks uniformity, controllability, and dispersibility, which dramatically decline their functional properties. Whereas the low‐quality ceramic powder reduces the device quality and affects industrial demand. To overcome these problems, using the sol‐hydrothermal technique is a practical and energy‐efficient way to produce very pure and homogenous powder.